PENGARUH CITRA MEREK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK VIVA KOSMETIK - Zainuddin, Muhammad Zabir; Manan, La Ode Abdul; Hertia, Hertia (Fakultas Ekonomi Dan Bisnis Universitas Sulawesi Tenggara, 2022)
Skin care or skincare has started to become a necessity due to the urge to have a better appearance. One of the cosmetic industries that has been successfully introduced to the wider community and still survives to this day is Viva Cosmetics. Viva cosmetics have a lower price, have a good brand image and are widely used by Indonesian women. Consumers today are very critical in choosing to buy a product. The purchase decision is one of the consumer's choices to determine the choice of something they want. The demand for an increasingly quality product makes every company compete to improve the quality of its products in order to maintain the brand image of the products they produce. Purchase decisions by consumers certainly involve the influence of the price of a product. According to Kotler (2015: 345) Price is the sum of all values provided by customers to benefit from owning or using a product or service. If the price offered is in accordance with the income of consumers, of course consumers will buy the product. Moreover, these products already have a good brand image, so that consumers will no longer doubt the products being marketed. This study uses multiple linear regression data analysis techniques using SPSS version 24.0 for Windows. Determination of the number of samples through purposive sampling technique, as many as 60 respondents. The results of the analysis prove that brand image and price have a positive and significant effect on purchasing decisions.